Towards a Sustainable Global Energy Supply Infrastructure: Net Energy Balance and Density Considerations - Kessides, Ioannis N.; Wade, David C. (2012)
This paper employs a framework of dynamic energy analysis to model the growth potential of alternative electricity supply infrastructures as constrained by innate physical energy balance and dynamic response limits. Coal-fired generation meets the criteria of longevity (abundance of energy source) and scalability (ability to expand to the multi-terawatt level) which are critical for a sustainable energy supply chain, but carries a very heavy carbon footprint. Renewables and nuclear power, on the other hand, meet both the longevity and environmental friendliness criteria. However, due to their substantially different energy densities and load factors, they vary in terms of their ability to deliver net excess energy and attain the scale needed for meeting the huge global energy demand. The low power density of renewable energy extraction and the intermittency of renewable flows limit their ability to achieve high rates of indigenous infrastructure growth. A significant global nuclear power deployment, on the other hand, could engender serious risks related to proliferation, safety, and waste disposal. Unlike renewable sources of energy, nuclear power is an unforgiving technology because human lapses and errors can have ecological and social impacts that are catastrophic and irreversible. Thus, the transition to a low carbon economy is likely to prove much more challenging than early optimists have claimed.